Human TLR8 Senses RNA From Plasmodium falciparum-Infected Red Blood Cells Which Is Uniquely Required for the IFN-γ Response in NK Cells - Coch, Christoph; Hommertgen, Benjamin; Zillinger, Thomas; Daßler-Plenker, Juliane; Putschli, Bastian; Nastaly, Maximilian; Kümmerer, Beate M.; Scheunemann, Johanna F.; Schumak, Beatrix; Specht, Sabine; Schlee, Martin; Barchet, Winfried; et al. (Frontiers in Immunology, 2019)
During blood-stage malaria, the innate immune system initiates the production of pro-inflammatory cytokines, including IFN-γ, that are critical to host defense and responsible for severe disease. Nonetheless, the innate immune pathways activated during this process in human malaria remain poorly understood. Here, we identify TLR8 as an essential sensor of Plasmodium falciparum-infected red blood cells (iRBC). In human immune cells, iRBC and RNA purified from iRBC were detected by TLR8 but not TLR7 leading to IFN-γ induction in NK cells. While TLR7 and 9 have been shown to lead to IFN-γ in mice, our data demonstrate that TLR8 was the only TLR capable of inducing IFN-γ release in human immune cells. This unique capacity was mediated by the release of IL-12p70 and bioactive IL-18 from monocytes, the latter via a hitherto undescribed pathway. Altogether, our data are the first reported activation of TLR8 by protozoan RNA and demonstrate both the critical role of TLR8 in human blood-stage malaria and its unique functionality in the human immune system. Moreover, our study offers important evidence that mouse models alone may not be sufficient to describe the human innate immune response to malaria.